2003
DOI: 10.1063/1.1556260
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetoresistance in (La1−xCaxMnO3)1−y:ZrO2 composite

Abstract: Magnetic properties of isotropic Sm-Fe-N magnets produced by compression shearing method J. Appl. Phys. 111, 07A716 (2012) Stable vortex magnetite nanorings colloid: Micromagnetic simulation and experimental demonstration J. Appl. Phys. 111, 044303 (2012) Evidence for low temperature glassy behavior in La0.5Sr0.5CoO3 J. Appl. Phys. 111, 043902 (2012) Temperature dependent phonon Raman scattering of highly a-axis oriented CoFe2O4 inverse spinel ferromagnetic films grown by pulsed laser deposition Appl. Phys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 13 publications
4
25
0
Order By: Relevance
“…This may be the possible reason for the increasing MR at lower temperatures especially in samples with x = 1/2 and 2/3. The overall MR behavior could be attributed to an intergrain tunneling mechanism [14]. The variation of magnetization (M) with temperature (T) for the series (La x Sm 1-x ) 2/3 Sr 1/3 MnO 3 (x = 1/3, 1/2 and 2/3) in a field of 100 Oe is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may be the possible reason for the increasing MR at lower temperatures especially in samples with x = 1/2 and 2/3. The overall MR behavior could be attributed to an intergrain tunneling mechanism [14]. The variation of magnetization (M) with temperature (T) for the series (La x Sm 1-x ) 2/3 Sr 1/3 MnO 3 (x = 1/3, 1/2 and 2/3) in a field of 100 Oe is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such composites with YSZ attracted a great deal of interest in view of their potential use in SOFC. The Pechini method has recently been used also for the preparation of similar composites containing La-manganite doped with Ba [17] and Ca [18,19]. Sr-doped composites of a similar type are synthesized in [20], but a modified sol-gel process using acetylacetone as a chelating agent (instead of citric acid) is employed.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of a single-phase product is often difficult and usually the particles of the final product are inhomogeneous in shape and size. Because of this, numerous methods for low-temperature synthesis have been proposed [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Coprecipitation of the metal nitrates solutions with aqueous ammonium carbonate is used in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is suitable addition of trivalent metal ion. Various studies on the substitution effect on magneto-transport have been reported [4,5]. However, most of them are dedicated to the bulk LCMO.…”
Section: Introductionmentioning
confidence: 98%